Productive forces in Karl Marx teaching - Pashkov, Vladimir P. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the content of the concept of productive forces in the main economic doctrine of K. Marx. The author criticizes the approach to its definitions as «system», «totality», «complex» of personal, subjective (human) and material (means of production) elements developed in economics. It is emphasized that the concept of force is a physical concept, it is included in the subject of theoretical physics. Productive force is a force (without its own definition) special, arising and operating in the sphere of material production only when the means of production are used by the working force. Definitions in textbooks, scientific papers that productive forces are tools of labour, means of production are erroneous.